Novel Concept of Aligning the Molecules for Electronic Paper Displays - Hegde, Gurumurthy; M. M., Yusoff; Chigrinov, V. G. (2013)
Flexibility is the way of future. Human mind is moving towards nanosize, so as devices. Future generation displays is more about electronic papers made up of plastic substrates. But the technology involved in this is rather complicated. Non-contact methods are only the solutions for generating future displays. On the otherhand, the phenomenon of liquid crystal photoalignment became a subject of extensive research after the effect was discovered for the azobenzene units attached to a substrate and dispersed in a polymer matrix. Since then, huge variety of alignment materials has been developed for photonics related applications [1, 2]. Nevertheless, azo dye materials remain among the best candidates for technological application. The LC alignment produced by rubbing is not perfectly uniform, especially on a microscopic level. Because of this, alignment methods avoiding mechanical contact with the aligning substrates are being actively studied. Photoalignment is among the most promising candidates due to their non-contact nature, high uniformity, wide-range and smooth variation of the parameters of LC alignment. Here we report first time the novel concept of photo aligning the surface of liquid crystals by unpoalrized UV light. Till today, all alignment method reported uses linear poalrized light to alignm the moelcules but we used unpolarized UV light to align the molecules which is unique and quiet straight forward method for device application is concerned. The proposed method is completely different than the method obtained so far in the industry or any academia or research groups.